Deep Learning‐Based Ion Channel Kinetics Analysis for Automated Patch Clamp Recording - Shengjie Yang; Jiaqi Xue; Ziqi Li; Shiqing Zhang; Zhang Zhang; Zhifeng Huang; Ken Kin Lam Yung; King Wai Chiu Lai (Advanced Science)
Abstract The patch clamp technique is a fundamental tool for investigating ion channel dynamics and electrophysiological properties. This study proposes the first artificial intelligence framework for characterizing multiple ion channel kinetics of whole‐cell recordings. The framework integrates machine learning for anomaly detection and deep learning for multi‐class classification. The anomaly detection excludes recordings that are incompatible with ion channel behavior. The multi‐class classification combined a 1D convolutional neural network, bidirectional long short‐term memory, and an attention mechanism to capture the spatiotemporal patterns of the recordings. The framework achieves an accuracy of 97.58% in classifying 124 test datasets into six categories based on ion channel kinetics. The utility of the novel framework is demonstrated in two applications: Alzheimer's disease drug screening and nanomatrix‐induced neuronal differentiation. In drug screening, the framework illustrates the inhibitory effects of memantine on endogenous channels, and antagonistic interactions among potassium, magnesium, and calcium ion channels. For nanomatrix‐induced differentiation, the classifier indicates the effects of differentiation conditions on sodium and potassium channels associated with action potentials, validating the functional properties of differentiated neurons for Parkinson's disease treatment. The proposed framework is promising for enhancing the efficiency and accuracy of ion channel kinetics analysis in electrophysiological research.